Relationship between Transport Anisotropy and Nematicity in FeSe - Jack M. Bartlett (American Physical Society, 2021)
The mechanism behind the nematicity of FeSe is not known. Through elastoresitivity measurements it has been shown to be an electronic instability. However, thus far measurements have extended only to small strains, where the response is linear. Here, we apply large elastic strains to FeSe and perform two types of measurement. (1) Using applied strain to control twinning, the nematic resistive anisotropy at temperatures below the nematic transition temperature T_{s} is determined. (2) Resistive anisotropy is measured as nematicity is induced through applied strain at fixed temperature above T_{s}. In both cases, as nematicity strengthens, the resistive anisotropy peaks at about 7%, then decreases. Below ≈40  K, the nematic resistive anisotropy changes sign. We discuss possible implications of this behavior for theories of nematicity. In addition, we report the following. (1) Under experimentally accessible conditions with bulk crystals, stress, rather than strain, is the conjugate field to the nematicity of FeSe. (2) At low temperatures the twin boundary resistance is ∼10% of the sample resistance, and must be properly subtracted to extract intrinsic resistivities. (3) Biaxial in-plane compression increases both in-plane resistivity and the superconducting critical temperature T_{c}, consistent with a strong role of the yz orbital in the electronic correlations.